A Methods engineering study of recon bakeshop - Barretto, Ronilon (College of Engineering, 1996)
Work Study concepts and techniques were applied to study the Recon Bakeshop, located in Taguig, Metro Manila. The Company's existing system was defined. The Method Study Approach was then applied to record and examine the existing systems of production. Time Study was also implemented in order to determine the standard time for each element in the production sequence. Problems encountered were worker and machine idleness, backtracking, presence of an inefficient layout, and poor worker and working environment hygiene. As consequences of these findings, the group proposes several alternatives : introduction of faucets, pest control, housekeeping and improved facilities design.